Dynamics and Sustainability of Environmental Conservation at Adiwiyata School in Malang. Issue 1 (1st July 2022) - Syaifulloh, M; Kodir, A; Zubaidah, S; Sumarmi,
Abstract: Environmental damages in Indonesia, in the past few decades, have been increasing as well as worrying. One of the responses emerged in dealing with these problems is to intensify environmental education. Internalization of environmental education within school curricula, in Indonesia, is executed through the Adiwiyata program. This study aims to describe the achievements, obstacles, and sustainability of Adiwiyata school's contributions to environmental conservation in Malang City. This research is a descriptive research. The research location is at SMAN 2 Malang City which has the status as an independent Adiwiyata school since 2017. Data collection was carried out by interview, observation and literature study methods. The results of the study indicate that environmental conservation is carried out not only in the internal context of the school. Environmental conservation is mainly focused on the sustainability of Brantas watershed. External parties involved in this project consist of the non-profit organization JKPKA, civil society, and stakeholders. There are several obstacles faced during the implementation of environmental conservation which are dominantly derived from the technical realm, namely parents' permitting issue and the locations. Strengthening of shared perceptions is indeed taken by the school to maintain the sustainability of environmental education.